THE FORM OF THE DYNAMICS OF CIVILIZATION CHANGES IN GIG BEBEGIG'S DANCE WORK: A STUDY OF DANCE THROUGH CHARLES SEMIOTICS. S. PEIRCE - Suryo Samudro, Rahmat; Wiebe Lau, Amy (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
Globalization has positive implications with ease through the development of technology. In line with technological developments, this also has an impact on the regeneration of farmers where young people no longer choose farming jobs. This problem was communicated by Farhan Apriadhi Ghazaly through the dance work of Gig Bebegig. This study uses a qualitative method that is described descriptively through the semiotic analysis of Charles S. Peirce and a socio-cultural perspective. The results of this study reveal the Representament-Object-Interpretant from wardrobe, music, property, and dance scenes, as well as see through a socio-cultural perspective.